Analisis Kontrastif Struktur Kalimat Arab Dan Indonesia Serta Implementasinya Dalam Pembelajaran - Mustolikh Khabibul Umam; Diah Ayu Kuswahyuningrum (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
This study aims to compare the pattern of the Jumlah Ismiyyah and Fi'liyyah in Arabic with subject+predicate in Indonesian in terms of meaning and provisions and its implementation in several appropriate methods. This study uses a qualitative method with a library research approach. Data collection uses the documentation method. The data analysis technique uses contrastive analysis that compares the pattern of the number of Ismiyyah and Fi'liyyah in Arabic with subject+predicate in Indonesian in terms of meaning and provisions. The results show: Among the similarities and differences in the number of Ismiyyah and Fi'liyyah and 'subject+predicate' are: a) the pattern of the number of ismiyyah such as the sentence